High strength and electrical conductivity of nanostructured Cu–1Cr–0.1Zr alloy processed by multi–stage deformation and aging - Chu, Zhuqi; Pan, Xuhao; Wei, Wei; Wei, Kunxia; Alexandrov, Igor V.; An, Xulong; Wang, Dandan; Liu, Xiangkui (Journal of materials research and technology, 2024)
The effects of equal channel angular pressing (ECAP), multiple cryogenic rolling and aging treatment on the microstructure, mechanical properties, and electrical conductivity of Cu–1Cr–0.1Zr alloy were investigated. The results showed that multi-stage deformation and aging (ECAP at ambient temperature + primary cryogenic rolling 50 % + 450 °C aging for 1h + secondary cryogenic rolling 80 % + 150 °C aging for 1h) can lead to the rational comprehensive performance of Cu–1Cr–0.1Zr alloy with tensile strength of 730 MPa and electrical conductivity of 75.5 % IACS. The microstructure characterization revealed that in the Cu–1Cr–0.1Zr alloy a subject to the multistage deformation and aging, there ultrafine grains, nanotwins, nanoprecipitates and micrometer precipitates constituted the nanostructured state. The increase in tensile strength was mainly attributed to fine grain strengthening and precipitation strengthening, followed by dislocation strengthening due to low temperature deformation. The ECAP resulted in the refinement of grain, and the increased dislocation density. The following primary cryogenic rolling refined the grains up to ultrafine-grained (UFG) size and created nanotwins. The introduction of nano-precipitated phases by intermediate aging pinned dislocations and impeded the motion of dislocation entanglements, allowing the alloy to achieve higher strength. Multi-stage deformation and aging resulted in a higher density of twin boundaries in the nanostructure and dilute solid solution in comparison with one stage treatment. These microstructural features were responsible for the excellent electrical conductivity. •A multi-stage deformation and aging process was proposed.•Incorporating high density dislocations, nanotwins, nanoprecipitates and micron precipitates, a multi-scale microstructure model was established.•An optimum combination of tensile strength of 730 MPa and electrical conductivity of 75.5 % IACS was successfully obtained.•The enhancement mechanism of high tensile strength and electrical conductivity was discussed.